Analysis of the distribution and the impact of drought on agricultural land in Sekotong District, West Lombok - Zuhdiyah Matienatul Iemaaniah; Zaki Muhammad Zamani (BIO Web of Conferences)
The existence of the El Nino phenomenon has an environmental impact, it causes low rainfall in the southern hemisphere, like Indonesia. Drought caused by El Nino is distributed throughout Indonesia, including Lombok Island. Sekotong District has an area surrounded by karst landforms and beaches. Karst areas cannot store groundwater so droughts often occur. Low rainfall and low water availability cause agricultural land to dry out so it cannot fill agricultural needs. This study aims to map the distribution of land affected by drought due to El Nino and its impact on agriculture in Sekotong District. The analysis of this study uses the Normalized Difference Drought Index (NDDI) analysis for the distribution of land drought and by conducting purposive interviews with farmers in Sekotong District. The results are the area of land drought class of around 2754.81 hectares without water shortage; 11,727.46 hectares in normal conditions; 11,715.31 hectares mild drought; 5313.1 hectares moderate drought; 1,606.62 hectares severe drought; and 1,144.57 hectares very severe drought. The impacts of this land drought include 1) Crop failure in rice commodities; 2) Agricultural land crops are substituted with peanuts and corn; 3) Agricultural land is not utilized at all because there is no water available.